A GATE/Geant4 beam model for the MedAustron non-isocentric proton treatment plans quality assurance. (March 2020) - Elia, Alessio; Resch, Andreas Franz; Carlino, Antonio; Böhlen, Till Tobias; Fuchs, Hermann; Palmans, Hugo; Letellier, Virgile; Dreindl, Ralf; Osorio, Jhonnatan; Stock, Markus; Sarrut, David; Grevillot, Loïc
Highlights: The treatment head design implemented in the MC beam model allows the characterization of the secondary spectra radiation. The beam model is calibrated in absolute dose based on a recent formalism in terms of a Dose-Area-Product within 1.2% The beam model is validated within clinical constraints including non-isocentric conditions. 33 non-isocentric clinical fields are reproduced within 1% when the average dose gradient is less than 1%/mm. The model serves as reference for future clinical as well as research work. Abstract: Purpose: To present a reference Monte Carlo (MC) beam model developed in GATE/Geant4 for the MedAustron fixed beam line. The proposed model includes an absolute dose calibration in Dose-Area-Product (DAP) and it has been validated within clinical tolerances for non-isocentric treatments as routinely performed at MedAustron. Material and Methods: The proton beam model was parametrized at the nozzle entrance considering optic and energy properties of the pencil beam. The calibration in terms of absorbed dose to water was performed exploiting the relationship between number of particles and DAP by mean of a recent formalism. Typical longitudinal dose distribution parameters (range, distal penumbra and modulation) and transverse dose distribution parameters (spot sizes, field sizes and lateral penumbra) were evaluated. The model was validated in water, considering regular-shaped dose distribution as well as clinical plans delivered in non-isocentric conditions. Results: Simulated parameters agree with measurements within the clinical requirements at different air gaps. The agreement of distal and longitudinal dose distribution parameters is mostly better than 1 mm. The dose difference in reference conditions and for 3D dose delivery in water is within 0.5% and 1.2%, respectively. Clinical plans were reproduced within 3%. Conclusion: A full nozzle beam model for active scanning proton pencil beam is described using GATE/Geant4. Absolute dose calibration based on DAP formalism was implemented. The beam model is fully validated in water over a wide range of clinical scenarios and will be inserted as a reference tool for research and for independent dose calculation in the clinical routine.